Bentuk Keterlibatan Masyarakat Dalam Upaya Penghijauan Pada Kawasan Hunian Padat di Kelurahan Serengan - Kota Surakarta - Rubiantoro, Eko Anton; Haryanto, Ragil (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Greening is an important activities that should be carried out conceptually in dealing the environmental crisis. Serengan Village is one of the kampung which is actively supporting the greening program in Surakarta. Community and relevant stakeholders have committed various greening activities efforts to rescue the environment in Serengan. The purpose of this study is to examine how the forms of community involvement in the greening efforts in high density residential areas in Serengan, Surakarta. This research was conducted using quantitative and qualitative approach with case study research strategy. Based on our research, we have knowed that the society has been involved in the planning, providing, maintening, and supervision of the greening activities. Serengan community assessed that the condition of the green space in the village is very minimal at this time. The greening activities was performed by community in various motives, such as: to increase the ecological value, to improve the aesthetic value, to get the economic benefit, andÂ  to support the government programs. The existence of stakeholders consisting of City Government, Local Government, Non-Government Institutions, Private/CSR, and Green Community/Academics have greatly contributed helping the development of greening activities in the study area.